Estudo do material lítico do Crasto de Palheiros - Murça : uma primeira abordagem metodológica - 2ª parte - Gomes, Isidro M. T. (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The final results from the study of lithic material from Castro de Palheiros (Murça-Vila Real) are presented in this manuscript, following the previous publication of the first data. The morpho-technical analysis of material such as, grindstones, polishers, adzes, axes and other tools, has been carried out. This material concerns the two main occupation phases: Chalcolithic (3rd millennium BC) and Iron Age (IVth century BC – Ist century AD).